2021
DOI: 10.1186/s40168-020-00960-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using alternative swabs and storage solutions for paired SARS-CoV-2 detection and microbiome analysis in the hospital environment

Abstract: Background Determining the role of fomites in the transmission of SARS-CoV-2 is essential in the hospital setting and will likely be important outside of medical facilities as governments around the world make plans to ease COVID-19 public health restrictions and attempt to safely reopen economies. Expanding COVID-19 testing to include environmental surfaces would ideally be performed with inexpensive swabs that could be transported safely without concern of being a source of new infections. Ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…Sample collection for SARS-CoV-2 RNA screening is typically performed using viral transport media containing fetal bovine serum and a cocktail of antibiotics, which could negatively influence studies of bacteria and other microbes [ 21 , 22 ]. For this study, swab samples were stored in 95% EtOH in order to inactivate the virus for safe transportation [ 23 ] while stabilizing the microbial community [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample collection for SARS-CoV-2 RNA screening is typically performed using viral transport media containing fetal bovine serum and a cocktail of antibiotics, which could negatively influence studies of bacteria and other microbes [ 21 , 22 ]. For this study, swab samples were stored in 95% EtOH in order to inactivate the virus for safe transportation [ 23 ] while stabilizing the microbial community [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation is the unknown recovery efficiency of SARS-CoV-2 RNA from the environmental samples. A recent study by Minich et al 30 on SARS-CoV-2 RNA recovery from swabs reported overall good recovery rates, and many factors were found to play a role (including swab type, storage solution, molecular processing), but especially the sampling itself. In our study, these factors remained the same throughout the study period, including collection of samples, which was strictly performed according to protocol by the same fieldworker, preventing potential differential errors.…”
Section: Discussionmentioning
confidence: 99%
“…If we consider low RNA loads in participating workers a proxy of viral excretion, 29–31 high shedding rates of SARS-CoV-2 for the majority are not to be expected; however, there might be individual differences and shedders among workers who were not tested. Most workers tested positive only pre-shift, which may be explained by physiological accumulation of respiratory tract secretions at the start of the day, 32 swabbing differences between testers, 33 and/or influence of stochastic processes especially at low viral loads (higher chance of false negatives). SARS-CoV-2 RNA level in the positive sewage sample was comparable with levels detected at urban sewage sites in the Netherlands in the early stage of the epidemic (March 2020) 34 .…”
Section: Discussionmentioning
confidence: 99%